Gene Correction of Point Mutations Using PolyPurine Reverse Hoogsteen Hairpins Technology - Félix, Alex J.; Solé, Anna; Noé, Véronique; Ciudad, Carlos J. (Frontiers in Genome Editing, 2020)
Monogenic disorders are often the result of single point mutations in specific genes, leading to the production of nonfunctional proteins. Different blood disorders such as ß-thalassemia, sickle cell disease, hereditary spherocytosis, Fanconi anemia and Hemophilia A and B are usually caused by point mutations. Gene editing tools including TALENs, ZFNs or CRISPR/Cas platforms have been developed to correct mutations responsible for different diseases. However, alternative molecular tools such as triplex-forming oligonucleotides and their derivatives (e.g. peptide nucleic acids), not relying on nuclease activity, have also demonstrated their ability to correct mutations in the DNA. Here, we review the Repair-PolyPurine Reverse Hoogsteen hairpins (PPRHs) technology, which can represent an alternative gene editing tool within this field. Repair-PPRHs are non-modified single-stranded DNA molecules formed by two polypurine mirror repeat sequences linked by a five-thymidine bridge, followed by an extended sequence at one end of the molecule which is homologous to the DNA sequence to be repaired but containing the corrected nucleotide. The two polypurine arms of the PPRH are bound by intramolecular reverse-Hoogsteen bonds between the purines, thus forming a hairpin structure. This hairpin core binds to polypyrimidine tracts located relatively near the target mutation in the dsDNA in a sequence-specific manner by Watson-Crick bonds, thus producing a triplex structure which stimulates recombination. This technology has been successfully employed to repair a collection of mutants of the dhfr and aprt genes within their endogenous loci in mammalian cells and could be suitable for the correction of mutations responsible for blood disorders.